PENGARUH CITRA MEREK DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN KONSUMEN MELAKUKAN PEMBELIAN PRODUK PAKAIAN (STUDI KASUS PADA SHOPEE) - HANNA MEILANI DAMANIK; MARTIN LUTER PURBA; HENDRIK E.S. SAMOSIR (JURNAL ILMIAH KOHESI, 2021)
This study aims to analyze how brand image and service quality influence consumer decisions in purchasing study clothingproducts at Shopee. The sampling technique used snowball sampling and analyzed by logistic regression. The results showthat the better the brand image in consumers perspective, the more likely consumers are to buy clothes on the Shopee siteand the better Shopee is able to serve consumer needs, the more likely consumers are to make purchases of clothes on thebuying and selling site.